2022
DOI: 10.1108/ijse-04-2021-0199
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Livelihood Empowerment Against Poverty (LEAP) program as a conditional income transfer: a search for a conceptual framework

Abstract: Purpose Ghana has implemented different kinds of pro-poor program and policies since its independence to reduce poverty. The Livelihood Empowerment Against Poverty (LEAP) is one of such program. LEAP is a social cash transfer program and its implementation has been under the auspices of the Ministry of Gender, Children and Social Protection since 2008. It provides direct cash and health insurance coverage for extremely poor households across the country to alleviate short-term poverty and encourage long-term h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Nirere (2022) found that social protection helps to manage the risk of the poor in Rwanda, even though social protection has not lifted the poor above the national poverty line, by analyzing the cash transfer program. Karakara and Ortsin (2022) found little or no impact of social protection on consumption by analyzing the cash transfer program in Ghana. However, there is a positive impact on non-consumption spending, such as children's schooling.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Nirere (2022) found that social protection helps to manage the risk of the poor in Rwanda, even though social protection has not lifted the poor above the national poverty line, by analyzing the cash transfer program. Karakara and Ortsin (2022) found little or no impact of social protection on consumption by analyzing the cash transfer program in Ghana. However, there is a positive impact on non-consumption spending, such as children's schooling.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Especially, education-related social protection coverage should be expanded to capture the issues of poor and extremely poor households since the universal system does not better target their difficulties. Karakara and Ortsin (2022) found that social protection has a positive impact on non-consumption expenditure such as education.…”
Section: Nature Of Povertymentioning
confidence: 99%
“…However, despite potential objective benefits, several hypothesised mechanisms could be driving unhappiness in these communities: (i) formalised less-vulnerable livelihood options can increase material aspirations, which if unmet can reduce happiness (Alem et al, 2014), (ii) lower social capital and trust in peri-urban areas could promote inequalities and individualistic wellbeing conceptualisations, which can increase relative comparisons to "better-off" households (Reyes-García et al, 2016;Tibesigwa et al, 2016), (iii) experience or fear of coastal climatic risks, such as flooding, can cause psychological damage and lower SWB (Sekulova & Van den Bergh, 2016), (iv) past state interventions, such as Livelihood Empowerment Against Poverty (LEAP) programmes in Sogakope, being removed without an effective exit plan can restrict long-term development goals and subsequently reduce happiness by creating a continued dependence upon state support (Karakara & Ortsin, 2022;Ohemeng et al, 2020;Osei-Tutu et al, 2020).…”
Section: Expenditure Poverty (Objective Wellbeing) and Unhappiness (S...mentioning
confidence: 99%